(untitled) (DINAMIS, 2023)
Brass material which generally has low corrosion properties and low frictional forces is very suitable for use as a construction material, piping, ammunition sleeves, jewelry and household appliances. Knowledge of strengthening the mechanical properties of brass materials is needed. In this study, the brass material was forged so that it experienced a volume reduction of 44% at three forging temperatures namely room temperature (28°C), 350°C and 450°C. To observe the impact strength, the brass material specimens were tested using the Charpy Impact tester. The ratio of energy absorbed for forged and unwrought brass specimens was observed using linear regression. The results of physical observations of the fracture pattern show a complete fracture, and the form of a grained fracture. which can be classified as brittle.